2018
DOI: 10.1186/s13643-018-0720-y
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to access and utilization of emergency obstetric care at health facilities in sub-Saharan Africa—a systematic review protocol

Abstract: BackgroundNearly 15% of all pregnancies end in fatal perinatal obstetric complications including bleeding, infections, hypertension, obstructed labor, and complications of abortion. Between 1990 and 2015, an estimated 10.7 million women died due to obstetric complications. Almost all of these deaths (99%) happened in developing countries, and 66% of maternal deaths were attributed to sub-Saharan Africa. The majority of cases of maternal mortalities can be prevented through provision of evidence-based potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(27 citation statements)
references
References 37 publications
1
25
0
1
Order By: Relevance
“…Several reports indicate that a large number of women tend not to attend basic antenatal care or delivery services in health facilities, but rather attempt to deliver at home or with traditional or faith-based birth attendants. As such, when women experience severe complications of pregnancy, they are brought to referral secondary or tertiary health care facilities for CEOC, sometimes in very dire conditions [4, 7, 8]. To date, the poor organization of CEOC in Nigeria has been well documented [8].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports indicate that a large number of women tend not to attend basic antenatal care or delivery services in health facilities, but rather attempt to deliver at home or with traditional or faith-based birth attendants. As such, when women experience severe complications of pregnancy, they are brought to referral secondary or tertiary health care facilities for CEOC, sometimes in very dire conditions [4, 7, 8]. To date, the poor organization of CEOC in Nigeria has been well documented [8].…”
Section: Introductionmentioning
confidence: 99%
“…Improved quality of care, particularly during the intrapartum period, can reduce preventable maternal and perinatal mortality. In many low‐ and middle‐income countries, failure to receive adequate care when a facility is reached, the third delay, 3 is exacerbated by lack of supplies, personnel shortages, long waiting times, and weak referral protocols 4 …”
Section: Introductionmentioning
confidence: 99%
“…In many low-and middle-income countries, failure to receive adequate care when a facility is reached, the third delay, 3 is exacerbated by lack of supplies, personnel shortages, long waiting times, and weak referral protocols. 4 Effective referral from primary health centers (PHCs) to hospitals offering comprehensive emergency obstetric and neonatal care is a critical component of quality maternity care. 5 Inter-facility referral relies on a confluence of factors, such as timely arrival of a woman in labor, appropriate identification of high-risk conditions by providers, emergency transportation, and communication between the referring and receiving facilities.…”
Section: Introductionmentioning
confidence: 99%
“…Sub-Saharan Africa alone accounts for 66% of deaths (201,000), followed by South Asia (66,000). In a meta-analysis published in 2018, Geleto et al [2], reported that between 1990 and 2015, about 10.7 million women died from obstetric complications. Yet, it is recognized that maternity associated risks can be reduced for all these women through the implementation of the 5th Millennium Development Goal (MDG).…”
Section: Introductionmentioning
confidence: 99%